A pure case study on moisture sensitivity assessment using tests on both loose and compacted asphalt mixture. (10th April 2020) - Haider, Safeer; Hafeez, Imran; Bilal Ahmed Zaidi, Syed; Ali Nasir, Muhammad; Rizwan, M.
Highlights: A pure case study (tests on loose as well as compacted asphalt mixture) was performed to access moisture sensitivity of asphalt mixture. Three different type of anti-stripping modifiers and aggregate sources were selected to prepare the asphalt mixture. Filler and chemical based modifiers were found relatively better than waste plastic modifiers. Moisture damage index shows a strong correlation between qualitative and quantitative test regime to access moisture damage of asphalt mixtures. Abstract: The main purpose of this research study was to predict moisture damage probability of asphalt mixtures using pure case study i.e. tests on loose as well as compacted asphalt mixtures. Polymer, chemical, filler-based modifiers and four aggregate sources i.e. calcium carbonate, dolomite, dolerite and granite minerals were selected to ascertain their effect on moisture damage of asphalt mixtures. Laboratory test results of both test regimes were compared to develop moisture damage index. The analysis of test data showed that filler-based modifiers were better anti-stripping followed by chemical-based modifiers. Moreover, granite minerals showed more loss of adhesion due to less polarity, hydrophilic and acidic nature of aggregates. Basic aggregates (calcium carbonate and dolomite) with its hydrophilic nature were relatively better antistripping. This is mainly due to its high polarity to make relatively stronger bond with asphalt binder. Boiling water test was easy to perform and less time consuming while rolling bottle test was found relatively more reliable in comparison with other tests on loose coated asphalt mixture. In compacted asphalt mixtures test regime, although Marshal stability was easy to perform, but Modified Lottman test as well as Hamburg wheel track test were found relatively better to access moisture susceptibility with reasonable confidence level. A pure case study was compromises of qualitative (tests on loose coated asphalt mixture) as well as quantitative (tests on compacted asphalt mixture) to ascertain relative accuracy of each test on moisture damage.